2021
DOI: 10.12968/bjon.2021.30.13.s19
|View full text |Cite
|
Sign up to set email alerts
|

Developing and piloting a simulated placement experience for students

Abstract: COVID-19 and rising student numbers are affecting healthcare education, particularly access to clinical placements. As healthcare education is increasingly supported by technology and non-traditional teaching methods, educational experiences gained through clinical placement also require new approaches. This article explores and discusses the use of a simulated clinical placement for a dietetic student cohort. During this virtual placement, students were able to explore and experience a virtual clinical settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Further advantages of this approach were described by Taylor et al (2021). They reported on an online simulation training experience that presented no risk to patient safety [ 27 ]. The nursing students taking part in the Elaine Study confirmed this finding and mentioned the possibility to learn without any pressure by having the opportunity to exercise their own practical competencies, as well as identifying their current existing deficits in a secure learning environment, as being significantly positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further advantages of this approach were described by Taylor et al (2021). They reported on an online simulation training experience that presented no risk to patient safety [ 27 ]. The nursing students taking part in the Elaine Study confirmed this finding and mentioned the possibility to learn without any pressure by having the opportunity to exercise their own practical competencies, as well as identifying their current existing deficits in a secure learning environment, as being significantly positive.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, Meyer et al proposed a modified transformative learning process regarding simulation training for healthcare students to create the best possible prerequisites for optimum dementia care in the future [ 28 ]. In the opinion of Taylor et al, these mentioned advantages are important fundamentals for enhancing the learning experience and creating effective, efficient clinicians in the future [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They offer a new method of simulation with the benefits of an 'anytime, anywhere' educational delivery, enabling multi-participant, immersive and realistic delivery of practice based interprofessional education at scale. Taylor et al (2021) discuss virtual placements as an alternative to traditional clinical placements, drawing on the example of a simulated clinical placement developed for dietetic students at Coventry University, where students immerse themselves in a virtual placement experience. While this innovation is profession-specific there are plans to develop and adapt the use of a virtual placement framework in a range of professions.…”
Section: Waterside General -From a Pop-up Hospital To Virtual Placementsmentioning
confidence: 99%
“…Research identifies the potential issues in practice (Taylor et al, 2021), where there are inequities in placement experiences for students that may form a barrier to skills and knowledge enhancement, thus proving detrimental to student learning. This may, in turn, disadvantage students in gaining the experiences they need to improve their chances of becoming a skilful nurse with the required evidence‐base to help save lives and improve patient journeys.…”
mentioning
confidence: 99%